Implications of Antibiotic Resistance in the Management of Helicobacter pylori Infection: Canadian Helicobacter Study Group. (1st November 2000) - Hunt, RH; Smaill, FM; Fallone, CA; Sherman, PM; van Zanten, SJ Veldhuyzen; Thomson, ABR
Abstract : Eradication of Helicobacter pylori from the gastric and duodenal mucosa is an important clinical goal in the treatment of infected patients with peptic ulcer disease and other H pylori -associated conditions. Although several oral drug combination regimens are associated with eradication rates of approximately 85% in controlled trials, the success rate in patients infected with a resistant strain of H pylori is closer to 75%. Resistance to metronidazole and clarithromycin, which are common components of combination treatment regimens, is of greatest concern. Reported rates of H pylori resistance to various antibiotics vary considerably. In Canada, the data documenting H pylori susceptibility are limited but suggest that resistance to these antibiotics varies geographically and within specific treatment groups. Although susceptibility testing is not a prerequisite for initial treatment of individual patients infected with H pylori, formal efforts to identify and monitor both the causes and prevalence of antibiotic resistance across Canada are a much needed step in the ongoing management of this important infection. Recommended treatment regimens may be useful, even for treating apparently resistant H pylori strains. However, it is important to understand the mechanisms of the development of resistant strains to manage patients with treatment failure better.